Antitrust vs. Privacy: the great dilemma in the new digital markets? - Díez Estella, Fernando; Ribera Martínez, Alba (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The digitisation of existing business models and the new way of doing business of digital platforms pose new challenges both to the performance of companies in the market and to the lives of consumers and users. The dominant digital companies are all American (Google, Facebook, Amazon, and Apple), and their practices appear to harm free competition in the markets. This phenomenon raises the challenge of how to deal with the regulation of Big Data, to which so far there has not been an entirely satisfactory response. This paper also analyses the constitutional content of privacy and its importance in the framework of competition analyses carried out on both sides of the Atlantic.
Keywords: Big Data; privacy; digital markets; antitrust